DNA barcoding of some commonly exploited fishes from the northern Western Ghats, India - QAYOOM, UBAID; PAWAR, RAVINDRA A; MOHITE, SWAPNAJA A; SAWANT, MILIND S; NIRMALE, VIVEK H; PAWAR, SHRIKANT P; GOSWAMI, MUKUNDA; LAKRA, WAZIR S (The Indian Journal of Animal Sciences, 2018)
The Western Ghats, being very rich in freshwater fish diversity, has recently been confirmed as a globally significant centre of diversity and endemism for freshwater species and comprise one of the 34 global biodiversity hotspots. Owing to its extreme ichthyofaunal diversity, the present study was designed to generate cytochrome oxidase I (COI) DNA barcodes for the identification of some commonly exploited fishes from the west-flowing rivers of northern Western Ghats. Twenty-three fish specimens representing 6 families and 10 species were barcoded from the major west-flowing rivers of the northern Western Ghats. The obtained barcodes discriminated all the species with sufficient barcode gap. The average Kimura two parameter (K2P) values for within species, the genus and family distances were 0.37, 17.74 and 18.51% respectively. The neighbour-joining tree revealed distinct clusters corresponding to the taxonomic status of the species. Generated barcodes are expected to provide the much-needed baseline reference for the ichthyofaunal biodiversity of the global biodiversity hotspot.